2022
DOI: 10.1007/s10266-022-00741-5
|View full text |Cite|
|
Sign up to set email alerts
|

Compressive strength evaluation of thin occlusal veneers from different CAD/CAM materials, before and after acidic saliva exposure

Abstract: In the present study are depicted valuable observations for practitioners, obtained from an in vitro study which aims to evaluate the compressive strength of occlusal veneers fabricated from 3 type of restorative materials, before and after 1 month of acidic artificial saliva exposure (pH = 2.939). In this context, 90 extracted human molars were prepared to receive computer-aided design/computer-aided manufacturing (CAD/CAM) occlusal veneers. The restorative materials considered in this study were: Cerasmart; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Some authors have observed lower crush resistance values when samples are stored in a low-pH artificial saliva. This type of test can also help determine changes inside composite materials subjected to the action of various factors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have observed lower crush resistance values when samples are stored in a low-pH artificial saliva. This type of test can also help determine changes inside composite materials subjected to the action of various factors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol used for the preparation of acidic artificial saliva was extensively described in the previous study published by our research group [ 43 ]. Briefly, the artificial saliva was obtained by weighing NaCl, KCl, CaCl 2 ·2H 2 O, and CO(NH 2 ) 2 in a mass ratio of 1:1:2:2.5 and dissolved in 1 L of distilled water, until a clear solution was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The findings of various investigations on the partial coverage of ceramic restorations are inconclusive. Even though most manufacturers advise posterior ceramic restorations to have a minimum thickness of 1.5 mm, several research studies have examined ceramic restorations with a thickness of 1.0 mm or even less that have excellent long-term clinical results [68][69][70][71][72][73][74].…”
Section: Investigations On Mechanical Propertiesmentioning
confidence: 99%